Anxiety and Depression among Hemodialysis Patient in a Tertiary Care Center Kathmandu, Nepal - Aryal, Nirmala; Roka, Tara; Oli, Supriya (Journal of Karnali Academy of Health Sciences, 2021)
Background: Anxiety and Depression is a common yet frequently overlooked psychiatric symptom in patient with End Stage Renal Disease (ESRD) treated with hemodialysis. The objective of the current study was to identify the proportion of anxiety or depression among patient undergoing hemodialysis in a tertiary care center. Methodology: A descriptive cross-sectional study design was adopted with sample size of 147. Consecutive sampling technique was used to select the sample. A semi-structured questionnaire and Hospital Anxiety and Depression scale was used. Collected data were analyzed by using both descriptive as well as inferential statistics. Result: We found 37% of the patients as having anxiety and 38% having depression, with 21% of co-morbidity. We found higher odds of anxiety among certain groups: female [adjusted odds ratio (aOR)-1.99, 95% CI: 0.78-5.09], respondents of 65 years and above age group (aOR-5.04, 95% CI: 1.24-20.55). The unemployed respondents had higher odds (aOR-3.54, 95% CI: 1.38-9.08) of co-morbid anxiety and depression. Also, those respondents who required hemodialysis twice to thrice a week had higher odds (aOR-6.79, 95% CI: 1.20-38.42). Conclusion: A substantial proportion of chronic kidney disease patients were having anxiety and depression and that this occurred more frequently among those undergoing dialysis. Likewise, female respondents, respondents of 65 years and above age group and unemployed respondents had higher odds of co-morbid anxiety and depression. So, effective and timely treatment of affective disorders and additional management of these associated comorbidities could enhance the quality of life of hemodialysis patient.